2012
DOI: 10.1186/1479-5868-9-147
|View full text |Cite
|
Sign up to set email alerts
|

Do major life events influence physical activity among older adults: the Longitudinal Aging Study Amsterdam

Abstract: BackgroundMajor life events are associated with a change in daily routine and could thus also affect habitual levels of physical activity. Major life events remain largely unexplored as determinants of older adults’ participation in physical activity and sports. This study focused on two major life events, widowhood and retirement, and asked whether these major life events were associated with moderate to vigorous physical activity (MVPA) and sports participation.MethodsData from the first (1992–93) and second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 35 publications
1
34
0
1
Order By: Relevance
“…There were 67 independent datasets used in the results. Three studies met our inclusion criteria but did not contain enough similar studies to create themes [29][30][31]. Overall, five studies met the criteria to be considered of high quality (14)(15), the majority of the studies (n = 57) were of moderate quality (10)(11)(12)(13), and 19 were identified as low quality (\10).…”
Section: Data Abstraction and Analysismentioning
confidence: 96%
“…There were 67 independent datasets used in the results. Three studies met our inclusion criteria but did not contain enough similar studies to create themes [29][30][31]. Overall, five studies met the criteria to be considered of high quality (14)(15), the majority of the studies (n = 57) were of moderate quality (10)(11)(12)(13), and 19 were identified as low quality (\10).…”
Section: Data Abstraction and Analysismentioning
confidence: 96%
“…To our knowledge, only one previous investigation, the French GAZEL study, has monitored physical activity levels repeatedly around the retirement transition [8], but the results might not necessarily be generalizable to other working populations because the large majority of GAZEL participants retired already at age 55 years with good pensions. A further limitation of the previous studies is imprecision due to the reliance on few repeat measurements, typically only one measurement before and one after retirement [7, 9, 10]. In addition, little is known about factors that may modify the effects of retirement on physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…This is a striking omission in the context of policy drives to extend working lives since ill health impacts negatively on hours of work and employment participation. There has been more research looking at the links between retirement and PA, and a positive association has been found in some studies (Koeneman et al 2012) but not all (Berger et al 2005;Slingerland et al 2007). It should be noted, however, that early retirees (55 -58) may leave work because of ill health (Rijs, Cozihnsen, and Deeg 2012) which could account for evidence that suggests leisure-time PA can increase with age (Lahti et al 2011) although the general trend is for PA to decrease with age (Sun, Norman, and While 2013).…”
Section: Introductionmentioning
confidence: 99%